Faktor Risiko Hipertensi pada Usia Dewasa dan Lansia - Mustajab, Abdullah Azam; Resmi, Dewi Candra (Fakultas Ilmu Kesehatan, 2025)
The transition of diseases that were initially dominated by infectious diseases has changed to non-infectious diseases, one of which is hypertension. Risk factors for hypertension are divided into two, namely unchangeable risk factors such as genetic factors, age and gender, while risk factors that can be changed such as lifestyle. The purpose of this study was to analysis risk factors for hypertension in adults and the elderly. Quantitative study method with correlation analysis on participants in Posyandu Bumiroso as many as 26 respondents with accidental sampling technique, respondents were measured for blood pressure and given a questionnaire for hypertension risk factors. Data were descriptively frequency analysis and chi square test was performed. The results showed that smoking obtained a p-value of 0.547, physical activity obtained a p-value of 0.347, fatty foods obtained a p-value of 0.031, family history of hypertension obtained a p-value of 0.016 and stress factors obtained a p-value of 0.037. The conclusion of the five factors studied, there were two factors that were not related to hypertension namely smoking and physical activity, while there were three factors related to hypertension namely fatty foods, family history of hypertension and stress.